ICCREM 2021 : Challenges of the Construction Industry under the Pandemic. - Wang, Yaowu (American Society of Civil Engineers, 2021)
This collection contains 112 peer-reviewed papers on risk and uncertainty in construction engineering and management presented at the International Conference on Construction and Real Estate Management 2021, held in Beijing, China, October 16-17, 2021.